Gambaran Densitas Mineral Tulang (DMT) pada Kelompok Dewasa Awal (19-25 Tahun) (Studi di Fakultas Kesehatan Masyarakat Universitas Diponegoro) - Mega Nur Cahyaningsih; Lintang Dian Saraswati; Sri Yuliawati; M. Arie Wuryanto (Jurnal Kesehatan Masyarakat (Undip), 2017)
Bone mass density (DMT) accounts for the greatest contribution to bone strength. The decrease in DMT will affect bone strength and early predictors of future osteoporosis. Center for Research and Development of Nutrition and Food MOHRI showed that osteopenia has attacked young age aged under 25 years with prevalence 37,1%. This study was conducted on 95 active students of FKM UNDIP aged 19-25 years with accidentally sampling technique, consisting of 15 men and 80 women. The study design used was cross sectional. Bone mineral density is measured by densitometry, height using microtoa, and body weight is measured using digital scales, physical activity is measured using a 2x24 hour Recall, and interviews to determine the profiles of respondents, knowledge, family history of osteoporosis, and menstrual cycle for women. The picture of DMT of FKM UNDIP students is osteoporosis 22,1% and osteopenia 21,1%, and normal category 56,8%. The average for Bone Mineral Density is -1.17 SD with the highest score of 4.18 SD and the lowest value of -7.53 SD. The average knowledge level was good (58,9%), as many as 20% of respondents had family member ever had osteoporosis, the most normal respondent IMT (72,6%) with mean of IMT 21,2 kg / m2. The level of mild physical activity was 57.9% with PAL 1.67, and menstrual cycle was 93.75% at most normal. Occurrence of osteoporosis and osteopenia in early adulthood (19-25 years) of students who have occurred need to be addressed with effective preventive measures